Peningkatan Kemampuan Pemecahan Masalah Matematis dan Self-Efficacy Siswa melalui Model Problem-Based Learning dengan Pendekatan Scientific - Dayat Hidayat; Muhammad Taufiqurrahman (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2022)
This research was motivated by the low ability of students’ mathematical problem solving and lack of their self-efficacy when learning mathematics. So, there was a need of learning model that is able to enhance students’ problem solving and self-efficacy. One of the learning models that can be used is Problem-Based Learning (PBL) mixed with scientific approach. This study aims to determine: (1) To compare mathematical problem solving ability of student who get the model PBL mixed with scientific approach and students who received conventional learning; (2) To compare the increase of students’ mathematical problem solving ability who get the PBL model mixed with scientific approach and students who received conventional learning; (3) To compare the students’ self-efficacy who get the PBL model with a scientific approach and students who received conventional learning; (4) To compare the increase of students’ selfefficacy who get the PBL model mixed with scientific approach and students who received conventional learning. The method used is a quasi-experimental method with population of eighth grade students of one of junior high school in Cilegon. Sampling is conducted through cluster random sampling technique. The results show: (1) Students’ mathematical problem solving ability of students who get the PBL model with scientific approach are better than students who received conventional learning; (2) The Improvement of students’ problem solving ability who get the PBL model mixed with scientific approach are better than students who received conventional learning; (3) students’ self-efficacy who get the PBL model mixed with scientific approach are better than students who received conventional learning; (4) The Improvement of students’ self-efficacy who get the PBL model mixed with scientific approach are better than students who received conventional learning. Keywords: Problem-Based Learning, Scientific Approach, Mathematical Problem Solving Ability, Self-Efficacy.